DETERMINAN INDEKS KEYAKINAN KONSUMEN TERHADAP KONDISI PEREKONOMIAN DI INDONESIA - Hasnidar Yuslin (Islamic Economic and Business Journal, 2022)
The condition of the prospects for the national economy is very influential for economic actors, both from producers, consumers, and investors. Early information regarding the prospects for the national economy is needed in all sectors, including government, small businesses, large-scale businesses, and even the wider community. This study analyzes Consumer Confidence Index to predict the economic prospects in Indonesia before and during the COVID-19 pandemic in the 2019-2021 period. The method used is descriptive statistical analysis. The results of this research analysis show that in 2019 before the Covid- 19 outbreak, consumer perceptions were maintained in the zone of optimism regarding the condition of the economic prospects in Indonesia, then during the 2020 pandemic in the second quarter, the pessimistic zone with the lowest index number compared to the other quarters, but consumer perceptions began to improve in the fourth quarter of 2020 until the fourth quarter of 2021. Optimistic consumer perceptions of 2021 in the second quarter and the next six months are in line with the government's optimistic attitude towards economic recovery and a reversal of direction towards positive.